2016
DOI: 10.1108/apjml-09-2015-0142
|View full text |Cite
|
Sign up to set email alerts
|

Physician perceived value as a mediating variable between marketing mix strategy and physician satisfaction

Abstract: Purpose Physician satisfaction (PHS) in the pharmaceutical business is a major issue that has created serious concerns for pharmaceutical companies and medical practitioners. The purpose of this paper is to explore the mediation effect of physician perceived value (PPV) on the relationship between marketing mix strategy (MMS) and PHS in the pharmaceutical industry in Yemen. Design/methodology/approach A non-probability purposive sample of 500 physicians was surveyed by using a self-administered questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(100 reference statements)
2
3
0
1
Order By: Relevance
“…Certain scholars had stated that providing customer value is one of the robust tools for creating and maintaining a competitive advantage (Kanagal, 2009;Lee & Overby, 2004). This study confirms that customer value can be created through effective adoption of marketing strategies that aim at providing greater benefits to end users (Bilington & Nie, 2009;Murshid, Mohaidin, Nee, & Fernando, 2016;Sangkaworn & Mujtaba). According to Lemon, Rust, and Zeithaml (2001), the convenience of a retail store minimizes the efforts of consumers for getting a certain product or service and this can influence their perceived value and overall purchase decisions.…”
Section: Conclusion and Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Certain scholars had stated that providing customer value is one of the robust tools for creating and maintaining a competitive advantage (Kanagal, 2009;Lee & Overby, 2004). This study confirms that customer value can be created through effective adoption of marketing strategies that aim at providing greater benefits to end users (Bilington & Nie, 2009;Murshid, Mohaidin, Nee, & Fernando, 2016;Sangkaworn & Mujtaba). According to Lemon, Rust, and Zeithaml (2001), the convenience of a retail store minimizes the efforts of consumers for getting a certain product or service and this can influence their perceived value and overall purchase decisions.…”
Section: Conclusion and Discussionsupporting
confidence: 73%
“…Finally, the outcomes of this research confirmed that store location has a significant positive impact on customer perceived value. The result was confirmed by a number of researchers (Li & Green, 2011;Murshid et al, 2016) who found that store location had a significant effect on perceived value. This study has some limitations which would offer opportunities for future researches.…”
Section: Conclusion and Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In recent times, the pharmaceutical market of Yemen is gradually becoming exposed to multinational drug companies. Drugs are increasingly being sold by different companies resemble each other, which leads to undue competition. In fact, each pharmaceutical firm utilises several marketing tools in an effort to persuade physicians to prescribe their drugs, frequently deviating from existing regulations.…”
Section: The Yemeni Pharma Marketmentioning
confidence: 99%
“…Satisfaction is one of the important issues in the long-term success and efficiency of companies and is considered as a prerequisite or consequence of many marketing activities (Nam et al , 2011; Murshid et al , 2016). From a cognitive perspective, satisfaction is the result of customers’ assessment of their experiences (Zhao et al , 2012).…”
Section: Part I: Qualitative Approachmentioning
confidence: 99%